1997
DOI: 10.1021/ja963682s
|View full text |Cite
|
Sign up to set email alerts
|

ESE-ENDOR and ESEEM Characterization of Water and Methanol Ligation to a Dinuclear Mn(III)Mn(IV) Complex

Abstract: Interactions of water and methanol with a mixed valence Mn(III)Mn(IV) complex are explored with 1H electron spin echo (ESE)-electron nuclear double resonance (ENDOR) and 1H and 2H ESE envelope modulation (ESEEM). Derivatives of the (2-OH-3,5-Cl2-SALPN)2 Mn(III)Mn(IV) complex are ideal for structural and spectroscopic modeling of water binding to multinuclear Mn complexes in metalloproteins, specifically photosystem II (PSII) and manganese catalase (MnCat). Using ESE-ENDOR and ESEEM techniques, 1H hyperfine par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
118
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(128 citation statements)
references
References 72 publications
10
118
0
Order By: Relevance
“…One interesting substrate water binding possibility arises from an examination of the hyperfine couplings in table 1. The class described in the first row, with the largest dipolar coupling and the shortest dipolar distance (2.59 Å ), also has an appreciable isotropic hyperfine coupling (3.58 MHz), which is consistent with it corresponding to a direct ligand to a paramagnetic Mn ion (Randall et al 1997). However, the class described in the second row, with a 2.71 Å dipolar distance, is simulated with only a dipolar coupling.…”
Section: Discussionmentioning
confidence: 58%
“…One interesting substrate water binding possibility arises from an examination of the hyperfine couplings in table 1. The class described in the first row, with the largest dipolar coupling and the shortest dipolar distance (2.59 Å ), also has an appreciable isotropic hyperfine coupling (3.58 MHz), which is consistent with it corresponding to a direct ligand to a paramagnetic Mn ion (Randall et al 1997). However, the class described in the second row, with a 2.71 Å dipolar distance, is simulated with only a dipolar coupling.…”
Section: Discussionmentioning
confidence: 58%
“…Studies of synthetic Mn complexes might elucidate the phenomenon. For instance, an ESEEM study indicates that methanol replaces water bound to a Mn III -Mn IV dimer (15).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the magnitude of the hyperfine coupling constants and energy of the transition, it was concluded that the OEC contained a mixed valence manganese cluster [112]. Subsequent analysis suggested that to simulate the OEC spectrum, one needed a cluster of at least three and then four manganese ions to match the EPR, ESEEM and ENDOR spectra [113][114][115]. Thus, this and related Mn III Mn IV species played a crucial role in our early understanding of the enzyme.…”
Section: Mn-μ-o 2 -Mnmentioning
confidence: 99%
“…The Mn-Mn separations remain within 0.1Å across this series (∼3.2-3.3Å) and the reduction potential for each successive compound shifts by ∼350 mV. A related series of compounds have also been prepared {[Mn III (2-OH-SALPN)] 2 (L)} which contain a terminal ligand such as water or alcohol [81,115,146,147]. These later compounds were particularly important for establishing the HBDEs for coordinated water protons.…”
Section: Mn-μ-o 2 -Mnmentioning
confidence: 99%